1994
DOI: 10.1016/0735-1097(94)90397-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary irradiation markedly reduces restenosis after balloon angioplasty in a porcine model

Abstract: Intracoronary irradiation (2,000 cGy) delivered to a target porcine coronary segment before balloon overdilation markedly reduces neointima formation at 30 days and thus significantly impairs the restenosis process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
9

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 300 publications
(82 citation statements)
references
References 31 publications
1
72
0
9
Order By: Relevance
“…Wiedermann and coworkers found suppression of neointima 4 weeks after angioplasty when 20 Gy was delivered at a radial depth of 1.5 mm just before arterial injury. 24 These same researchers demonstrated a persistence of this effect in arteries harvested at 6 months. 25 Similarly, our group at Emory demonstrated profound suppression of neointima using 192 Ir with a dose-response effect in vessels treated with 3.5, 7, and 14 Gy at a radial depth of 2 mm, and continued benefit at 6 months in arteries treated with 7 and 14 Gy.…”
Section: B Catheter Based Irradiation Studiesmentioning
confidence: 90%
“…Wiedermann and coworkers found suppression of neointima 4 weeks after angioplasty when 20 Gy was delivered at a radial depth of 1.5 mm just before arterial injury. 24 These same researchers demonstrated a persistence of this effect in arteries harvested at 6 months. 25 Similarly, our group at Emory demonstrated profound suppression of neointima using 192 Ir with a dose-response effect in vessels treated with 3.5, 7, and 14 Gy at a radial depth of 2 mm, and continued benefit at 6 months in arteries treated with 7 and 14 Gy.…”
Section: B Catheter Based Irradiation Studiesmentioning
confidence: 90%
“…6,7,70,71,75) Wiedermann and co-workers found suppression of neointima 4 weeks after angioplasty when 20 Gy was delivered at a radial depth of 1.5 mm just before arterial injury and demonstrated that this effect persisted at 6 months. Similarly, Waksman and co-workers demonstrated profound suppression of neointima using 192 Ir with a doseresponse effect in vessels treated with 3.5, 7, and 14 Gy at a radial depth of 2 mm.…”
Section: Studies Of Endovascular Irradiationmentioning
confidence: 99%
“…To evaluate the proper method to apply this new modality of treatment, several investigators have used both externally delivered X ray-irradiation as well as various catheter-based and radioactive stent endovascular approaches with various isotopes in experimental studies primarily using pigs and rabbits. 6,7,70,71) …”
Section: Preclinical Studies Using Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ICBT delivers radiation locally to the arterial wall at the time of angioplasty or stenting by means of catheter-based delivery systems using ␥ or ␤ irradiation sources, with demonstrated efficacy in reducing the incidence of restenosis. [7][8][9][10][11][12][13][14] The mechanism by which ICBT inhibits restenosis is not fully understood, but it appears to involve reduced smooth muscle cell (SMC) proliferation and delayed healing responses to vascular injury. 14,15 Macrophage colony-stimulating factor (M-CSF) is a multifunctional proinflammatory protein that regulates the differentiation, proliferation, and survival of mononuclear phagocytic lineage cells such as macrophages and SMCs.…”
mentioning
confidence: 99%